Educational games as a strategy to strengthen motivation in students from Octavo año de Educacion Básica from “Unidad Educativa Intercultural Bilingüe Monseñor Leonidas Proaño” in city of Riobamba, Province of Chimborazo, during the Academic Period 2021-2022 - Hinojoza Pilamunga, Ruth Stefanny (2022)
The strategies applied in the classroom play a fundamental role in the teaching and learning process, which is why the implementation of educational games is an innovative and fun strategy that helps motivate students when acquiring new knowledge, especially if it is a foreign language. Educational games break the tension that exists inside the classroom or between teacher and student, and help students have a good time while learning consciously or unconsciously. Therefore, this research project seeks to analyze how educational games as a strategy strengthen eighth grade students' motivation from " Unidad Educativa Monseñor Leonidas Proaño” of Riobamba city in the academic period 2021-2022. For this purpose, exploratory research was applied in order to know how educational games applied in English classes motivate students to learn and develop freely while playing. The results of the research indicate that innovative strategies such as educational games encourage creativity, autonomy, spontaneous use of language, and critical thinking of the student.